COVID-19 Confinement and Health Risk Behaviors in Spain - López-Bueno, Rubén; Calatayud, Joaquín; Casaña, José; Casajús, José A.; Smith, Lee; Tully, Mark A.; Andersen, Lars L.; López-Sánchez, Guillermo F. (Frontiers in Psychology, 2020)
The World Health Organization (WHO) declared a world pandemic due to COVID-19. In response, most affected countries have implemented enacted measures involving compulsory confinement and restrictions on free-movement, which may have collateral consequences for public health due to unhealthy lifestyle. This study investigates the time-course of confinement with changes in health risk behaviors (HRBs). An online survey served to collect data about the Spanish adult population regarding health habits during the first three weeks of confinement. A large sample of participants (N=2741) (51.8% women) aged 34.2 years (SD 13.0) from all Spanish regions completed the survey. Binomial logistic regressions controlled for socioeconomic characteristics (i.e. gender, age, civil status, education, and occupation), body mass index (BMI), previous HRBs and confinement context (i.e. solitude and exposure to COVID-19) were conducted to check associations between number of weeks confined and a set of six HRBs (physical activity, alcohol consumption, fresh fruits and vegetables consumption, smoking, screen exposure and sleep hours). When adjusted, we observed significant lower odds of experiencing HRBs overall in a time-dependent fashion; OR 0.63; 95%CI: 0.49-0.81 for the second, and OR 0.47; 95%CI: 0.36-0.61 for the third week of confinement. These results were equally consistent in all age and gender subgroup analyses. The present study indicates that HRBs of Spanish adults improved during the first three weeks of COVID-19 confinement. The population may adapt to the new situation context by gradually improving health behaviors, thus reducing the risk of collateral public health damage.